Transforming Islamic Religious Education Through the TPACK Approach in the Digital Era - Nurul Habibah Arfizeah; Sri Murhayati; Hafizah (KIPS Institute, 2025)
The development of the digital era requires teachers, especially in Islamic Religious Education (PAI), to be able to integrate technology in the learning process. However, many teachers still face obstacles in effectively integrating aspects of technology, pedagogy, and content. This study aims to analyze PAI teachers' understanding of the concept of TPACK and its implementation in the learning process. The method used is library research by reviewing relevant literature in the form of books, journals, and scientific articles. The results show that TPACK provides a comprehensive framework for teachers to synergistically combine technology, pedagogy, and content. The application of TPACK in PAI is able to create interactive, contextual, and learning that is in accordance with the characteristics of students in the digital era, as well as assisting teachers in choosing learning strategies that suit their needs. Nonetheless, dynamic technological developments require teachers to constantly adapt and update their skills. In conclusion, this research emphasizes the importance of mastery of TPACK by PAI teachers as a strategy to increase the effectiveness and relevance of religious learning in the midst of ever-evolving technological advances.